Perilaku Nilai Kuat Tekan Bebas pada Tanah Ekspansif Kabupaten Tangerang - Putera Agung Maha Agung; Aida Nurfitria; Aldo Wirastana Adinegara; Zaindra Fakhri Salim (Indonesian Society of Applied Science, 2026)
Expansive soil is a type of soil that often causes problems in construction due to its ability to swell and shrink due to fluctuations in moisture content. This study evaluates the behavior of an expansive soil sample from Kranggan Road, Cisauk Subdistrict, Tangerang Regency, using the laboratory unconfined compressive strength (UCT), including its physical properties. The unconfined compressive strength testing is needed to determine (qu) values of expansive soils. Road damage due to the expansive soil would cause some cracks and/ or pavement surface damage in a short time. The research aims to find the deformation behavior based on the plasticity index (PI) and (qu) value using PLAXIS 2D. The results show that the expansive soil could be classified as montmorillonite inorganic clay with a high value of plasticity index (PI) of 35.30%. Unconfined compression value was 3.53 kg/cm2 and 2.89 kg/cm2 in compacted and remoulded conditions, respectively. Magnitude of deformation during the rainy season indicated that a heave deformation of 0.14 mm and the settlement reached 0.47 mm with an SF value of 1.10. The maximum of a heave deformation value was 0.14 mm and 0.30 mm for settlement with a safety factor (SF) value of 1.30 during the dry season.